+0  
 
0
45
2
avatar

\(\begin{align*} 4(m - n) &= 7(1 - n),\\ \frac{3}{2}n&= 4-2m. \end{align*}\)

 Mar 13, 2021
 #1
avatar+311 
+1

I've thought about it for like 3 seconds, and I don't think there is a solution.

 

If I solve any of the first variables, then substitude that result into the other equation, there's no solution.

 

Yeah uhh.

 

m=(7-3n)/4 

 

m=-(3n)/4+2 as well

 

Yay!

 Mar 13, 2021
 #2
avatar+118069 
+1

4m  - 4n   =  7  -   7n       rearrange  as

 

4m +  3n  =  7

 

The  second equation  can be rearranged  as

 

2m + (3/2)n   =  4           multiply   through  by  2

 

4m  + 3n   =  8

 

As  Varxaax   has  duly noted, there is  no solution

 

We  can't  add    4m + 3n     and    get  two different  quantities

 

Good job, Varxaax   !!!!!

 

 

 

cool cool cool

 Mar 13, 2021

35 Online Users

avatar
avatar
avatar